Trust and Business Transaction - Pheni Chalid (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
Aim of this paper is to explore the root and role of trust within business cycle and transaction. Any business and social transactions contain complexity and are built on the basis of trust and rational calculation. Fluctuation of price of any commodities and level of their selling products are determined by the degree of consumers’ trust. Lessons learned from the field teaches that the trust easy to be gone and hard to be re-treated. Keeping trust is very important since any transactions tend to face business failure but existing trust in business commitment will diminish the risk of losing. It is reason why businessmen rely on not only rational calculation but also on emotional, cultural and ethnicity based of trust.If not, it will engender serious risk. DOI: 10.15408/sjie.v5i2.3393